Pengaruh Mekanisme Gamifikasi Terhadap Brand Equity Melalui Brand Engagement (Studi Kasus: Jabodetabek) - Daniel Nugraha; Jarot Sembodo Suroso (Jurnal Informasi dan Teknologi, 2023)
Gamification is now a well-liked marketing strategy. Many businesses think that gamification has the potential to raise consumer engagement, brand awareness, and brand loyalty. Beyond the pervasive hype, there is currently a lack of empirical evidence that supports these beliefs. In this study, we investigated the connections between gamification, brand equity, and consumer brand engagement among GoClub Application users (N = 407). The findings revealed that all three types of brand engagement were positively correlated with achievement and social gamification features (emotional, cognitive, and social). Brand equity was additionally positively correlated with brand engagement. The findings suggest that gamification can enhance brand engagement and build brand awareness, and that it appears to be a successful brand management strategy.